Environmental quality and health outcomes in sub-Saharan Africa- A panel econometric approach on the role of forest investment - Ovikuomagbe Oyedele; Sheriffdeen A. Tella (Cogent Economics & Finance, 2023)
Beyond the economic support in terms of food, fuelwood, charcoal, wood, and timber supplies that investment towards forest environments provides, its contribution to environmental quality could also provide health benefits. Using data from 16 selected sub-Saharan African countries from 2002 to 2016, this study examined the effect of environmental quality on health outcomes with specific consideration for forests. Employing different panel estimation methods for robustness and conducting a sub-sample estimation for sensitivity analysis, the results showed that forest expansion initially seemed to worsen health outcomes; however, after a turning point, it ultimately improved health outcomes as shown by its reduction effect on under-five mortality and its increasing effect on life expectancy at birth. Policies towards improving population health should consider forest expansion and conservation reforms.
Keywords: Q2; Q5; 330; environmental quality; forest investment; health outcomes; life expectancy at birth; sub-Saharan Africa; under five mortality